Pengaruh Rumah Sehat terhadap Kejadian Stunting pada Balita di Dusun Patinia Kec. Seram Barat - Ety Dusra; Epi Dusra (Pusat Riset dan Inovasi Nasional, 2025)
Stunting can lead to serious health problems in children, such as impaired growth and development. Growth retardation or stunting in early childhood can affect both the physical and mental capabilities of a child. In addition, stunting also increases the risk of illness, mortality, and delays in motor and cognitive development. Inadequate household sanitation can further increase the likelihood of such health issues. One of the indirect causes of stunting is poor environmental conditions, which allow the occurrence of infectious diseases such as diarrhea and respiratory infections, thereby contributing to the incidence of stunting. The objective of this study is to determine whether there is an influence of healthy housing on the incidence of stunting among toddlers in Dusun Patinia, West Seram District, West Seram Regency. The research design used is a non-experimental descriptive correlation study with a cross-sectional method. The population and sample in this study consisted of 50 family members with toddlers. The results of the analysis using the Pearson Product Moment test showed that there is a significant influence of healthy housing on the incidence of stunting among toddlers in Dusun Patinia, with a p-value of 0.001. This indicates that statistically, there is a meaningful relationship between healthy housing and the incidence of stunting in toddlers. Conclusion: Healthy housing has an influence on the incidence of stunting in toddlers in Dusun Patinia.